DAMPAK KELELAHAN TERHADAP HASIL TENDANGAN PENALTI PADA PEMAIN FUTSAL - Jannah, Miftahul; Zaky, Mohamad; Haryono, Tono; Imanudin, Iman; Umaran, Unun; Kurniawan, Tian; Hidayat, Iwa Ikhsan (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2025)
The purpose of this study was to determine the impact of fatigue on the results of pinalty kicks on futsal players. This study uses the Pre-Experimental method in a one-group pretest-posttest design, one group is measured or observed not only after being exposed to a type of treatment, but also before. The population used in this study were 12 members of the women's futsal club Futsal 35 who already had 2-3 years of experience. The instrument used in this study was the R.A.S.T Test 6 x 35m. Running-based Anaerobic Sprint (RAST) and lactic acid measuring instrument. The results of data processing and analysis showed the lactate value of 12 people before fatigue with a value of 17.67 mmol / l, and the lactate value after fatigue amounted to 127.75 mmol / l. However, the results have been tested using the RAST test. However, the results that have been tested using the paired sample t test can be explained that there is no difference in the results of penalty kicks against the results with a P value (0.027) > 0.05. This shows that there is no significant effect of the impact of fatigue on the results of penalty kicks in futsal players. Keyword: Fatigue, Penalty Kick, Futsal